The Ecuadorian industry and the Andean FTA - Luna Osorio, Luis (2016)
This article looks at the behavior of the industrial sector within the context of the Ecuadorian economy and posits some key elements for an industrialization policy. It is emphasized that a National Development Plan is needed, so as to outline a long-term policy which could facilitate the expansion and modernization of several domestic economic sectors. The perspectives of the different industrial activities within the US-Andean Free Trade Agreement are also analyzed.